2005
DOI: 10.2108/zsj.22.501
|View full text |Cite
|
Sign up to set email alerts
|

Enterotoxin/Guanylin Receptor Type Guanylyl Cyclases in Non-Mammalian Vertebrates

Abstract: ABSTRACT-Cyclic GMP is a ubiquitous intracellular second messenger produced by guanylyl cyclases (GCs). The enterotoxin/guanylin receptor type membrane GC (designated as GC-C in mammals) is activated by exogenous ligands such as heat-stable enterotoxins (STa), small peptides secreted by some pathogenic strains of Escherichia coli which cause severe secretory diarrhea and also activated by endogenous ligands such as guanylin and uroguanylin. The STa/guanylin receptor type membrane GC, as well as other type memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…Gene disruption studies revealed that GC-C is the physiological receptor for STa, because null mice are resistant to infections by enterotoxigenic bacteria that would otherwise kill wild-type mice (Schulz et al, 1997). Recently, it was demonstrated that fish species such as medaka fish (Oryzias latipes) and eel (Anguilla anguilla) contain two homologues of mammalian GC-C, one of which (OlGC9) is activated by STa but not by endogenous ligand(s), and that the transcription of the endogenous ligand-activatable GC (OlGC6) is regulated by OlPC4, a medaka fish homologue of mammalian transcriptional positive co-factor (PC4) (reviewed by Nakauchi and Suzuki, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Gene disruption studies revealed that GC-C is the physiological receptor for STa, because null mice are resistant to infections by enterotoxigenic bacteria that would otherwise kill wild-type mice (Schulz et al, 1997). Recently, it was demonstrated that fish species such as medaka fish (Oryzias latipes) and eel (Anguilla anguilla) contain two homologues of mammalian GC-C, one of which (OlGC9) is activated by STa but not by endogenous ligand(s), and that the transcription of the endogenous ligand-activatable GC (OlGC6) is regulated by OlPC4, a medaka fish homologue of mammalian transcriptional positive co-factor (PC4) (reviewed by Nakauchi and Suzuki, 2005).…”
Section: Introductionmentioning
confidence: 99%